O paradeiro dos soldados desertores da Colônia Militar Pedro II. - Débora Bendocchi Alves (Centre de Recherches sur les Mondes Américains, 2017)
In 1840, the Brazilian Empire established the Military Colony Pedro II on the banks of the Araguari River, situated at the northern extremes of its vast territory. This was the first of a series of military settlements throughout the country. Some years later, in 1855, some soldiers from the settlement rebelled, killing the director and escaping to the Franco-Brazilian frontier, a region contested by the Brazilian and French empires. Through an examination of official correspondence, this work draws attention to the difficulties that Brazil faced in recuperating deserters who had taken refuge into this territory and even in French Guyana. As the documentation provides us with the identity and whereabouts of these men, I consider the importance of recuperating the strategies they employed to maintain their freedom, and thus the complex social and political networks into which they had become involved.